Increased Growth of Kume Grass (S. plumosum) and B. pertusa Through the Introduction of Various Types of Herbaceous Leguminosae - A. D. Firmanto; E. Hartati; I.G.N. Jelantik (Jurnal Sain Peternakan Indonesia, 2022)
This study aims to determine the interaction between age and leguminous to the growth of grass S. plumosum (Sp) and B. pertusa (Bp). Both types of grass are planted in 18 plots measuring 2x2m2 with a distance of 60 cm between plots. The study was conducted using a completely random design of factorial patterns with two factors. The first-factor plant typically consists of 6 levels, namely Co, Clitoria ternatea (Ct), Pueraria phasoloides (Pp), Centrocema pubescent (Cp), Desmodium incanum (Di), and Alysicarpus vaginalis (Av). The age of cutting as a second factor consists of 3 levels, namely 40, 60, and 80 days and repeated three times. Variables measured the number of spouts, the height of the plant, and the number of leaves. Data analysis is done using the SPSS software package version 25. The level of significance adopted is P<0.05. The results showed there was an interaction (P<0.05) towards the height and number of SP leaves, while in the number of saves Sp Bp, high and the number of bp leaves, there was no interaction (P>0.05).